Smt. Gandhi Amidst Birds of Bharatpur - Saxena, V. S. (Indian Forester, 1976)
Prime Minister, Mrs. Indira Gandhi went round the Bharatpur Bird Sanctuary on 8th Feb., 76 for over 3 hours in the boat and the minibus. Padma Vibhushan Dr. Salim Ali was also with her. The author was the only forest officer accompanying her. She saw 85 spp. of birds of which she herself recognised about 50 spp. Among wild animals were seen numuerous spotted deer, blue bulls, jackal besides wild cows. She evinced keen interest in flora also. On ’wildlife management topics, she expressed that sanctuaries should not have posh buildings, visitors should not come with transistors and in gaudy dresses live bait should not he provided to tiger at least in the sanctuaries, thoroughfares bringing buses and noises into the sanctuary should not be permitted, plantations should be raised if treeS were dying and for culling unrestricted growth of uagulates why predators like panthers could not be introduced. On the whole she had a delightful, peaceful and interesting experience in the sanctuary.